Attribution analysis of changing pan evaporation in the Qinghai–Tibetan Plateau, China. (13th February 2018) - Zhang, Cungui; Liu, Fenggui; Shen, Yanjun
ABSTRACT: Pan evaporation ( E pan ) is reported to have exhibited a decreasing trend in many regions of the world over the past several decades. However, recently, the latest studies have discovered the inconsistent phenomenon that the E pan of some regions showed an increasing trend with climate change. E pan is regarded as a critical indicator that plays a significant role in atmospheric evaporative demand, and its trend has an important significant indication to climate change and ecological environment changes. In this article, we adopted the PenPan model and the method of the total short‐wave irradiance of the pan to reparameterize the PenPan‐20 model for the Qinghai–Tibet Plateau (QTP). In addition, we employed sensitivity and a contribution model to analyse the attribution of changes in E pan under climate change over the QTP in 1970–2011. The results showed that the PenPan model can be applied to QTP. Furthermore, the results showed significant decreasing trends of E pan in 1970–2001 and insignificant increasing trends of E pan in 2002–2011. Therefore, we compartmentalized the two periods to analyse the cause of changing E pan by sensitivity and contribution rate. Trend analysis determined that the combined effects of decreasing net radiation and wind speed contributed to the decreasing of E pan in 1970–2001, and the increasing vapour pressure deficit contributed to the increasing of E pan in the study area in 2002–2011. Meanwhile, sensitivity analysis revealed that net radiation was the most sensitive factor. In addition, the results of analysis of the contribution rate were consistent with trend analysis. The dominant factor of changing E pan varied in different periods via qualitative and quantitative analysis. Abstract : Distribution of meteorological sites and elevation of the Qinghai–Tibetan Plateau.